Influence of the period of maturation on the production of hard seeds in Centrosema pubescens - Serpa, Aryno; Achicar, José (Pesquisa Agropecuaria Brasileira, 2014)
Studies on the intumescence of seeds of Centrosema pubescens Benth. at a constant temperature of 28°C were made in a tray germinator. Six different collections were made, each 10 days later than the previous collection. Mature seed was collected, dried for 17 hours at 50°C and examined with a 30X lupe to eliminate scarified seed. Seeds were placed in the germinator exactly 85 days after collection. A completely randomized split split plot design with two replications was used to test results. Periods of collection were designated as plots. Subplots were 200 seeds of each seed group (heavy, medium and light). The sub-subplots were the numbers of the four counts for each period. Analysis showed highly significant differences (P < 0.01) between periods of collection, counts and interaction (Periods x group and period x count). Interaction of group x count was only significant (P < 0.05). Seeds classified as hard showed no problem of dormancy 14 days after scarification.